Hindi ito TV Patrol A case study of vertical-format news explainers by Patrol ng Pilipino 2023-2024 - Cristy, Kyle Angelo L.
As consumers of legacy media continue to decline, more and more people are shifting to online platforms to access information. In the Philippines, social media apps remain the leading sources of news, with TikTok placing fourth in the list despite its relatively recent popularity. Due to this shift in the media landscape, news organizations were forced to adapt to emerging trends and platforms to chase their audience, stay relevant, and continue delivering information. Guided by the Media Richness Theory and Social Media Logic, this study analyzed how Patrol ng Pilipino (PnP), a mobile journalism platform by the media giant ABS-CBN, produced news explainers that fit the demands and audience of vertical-format platforms like TikTok. Specifically, content analysis and interviews were conducted to identify the multimedia elements and discuss why these are incorporated in PnP’s explainers. The study found that despite the change in platform and orientation, PnP’s vertical-format explainers still heavily rely on traditional audiovisual elements like standuppers and voice-overs. Notably, informal approaches and deviations from television were observed, including the use of skits, background music, and sound effects. The study also found that while PnP’s explainers are “media-rich,” there are untapped potentials to be explored in terms of TikTok-specific affordances that may result in better interactivity and virality.